Hubungan Frekuensi Konsumsi Sayur dan Buah dengan Status Gizi pada Guru dan Staff SMP Negeri 22 Surakarta - Nasywa Nadhifa Qonita Putri; Firmansyah, Firmansyah; Nur Lathifah Mardiyati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to analyze the relationship between the frequency of vegetable and fruit consumption and nutritional status among teachers and staff at SMP Negeri 22 Surakarta. This study was conducted in December 2025 using an analytical survey research design and cross-sectional method. The sample of this study consisted of 32 respondents selected using a simple random sampling technique. The data collected included information on gender, age, weight, height, vegetable and fruit consumption, and nutritional status of respondents. Data analysis was performed using univariate and bivariate statistical tests, with the Shapiro-Wilk normality test and Pearson correlation and Spearman Rank according to the data distribution. The results showed that the frequency of vegetable and fruit consumption did not have a significant relationship with nutritional status among teachers and staff at SMP Negeri 22 Surakarta, with a p-value of 0.153. This study contributes to understanding the factors that influence nutritional status in educational environments and encourages further research with a larger sample size and considering other variables such as physical activity and other nutritional intakes.